Access cookbook - Getz, Ken (O'Reilly, 2002)
Access Cookbook contains a comprehensive collection of problems, solutions,and practical examples for the Access power user or programmer who is running up against some of the apparent limits of the Access user interface or of Access application development. The diverse problems and solutions presented here are of interest to Access power users and programmers at all levels, from the relatively inexperienced to the most sophisticated. Each of the book?s 14 chapters focuses on a particular topic area related to the Access environment or Access programming. Within each chapter, individual items follow a standardized format. The authors first pose the problem, and then present its solution. Finally, a discussion follows, which consists of extended analysis of the solution, an insightful examination of how Access works, or interesting programming techniques that are used in the solution but that you can also apply elsewhere. The kinds of problems posed and solved in the book include the following: Specifying query criteria at runtime, rather than at design time Restricting the user to a single row of a form Preventing a report from printing if it has no records Making slow forms run faster Insuring that user interface objects present a uniform, consistent appearance Controlling a printer's paper source programmatically Referencing data from multiple SQL Server databases in a single Access Data Project page Using contact information from an Access database when sending email using Outlook The accompanying CD-ROM includes Access databases that contain the solutions for all problems presented in the text.